Trust in Corporate Social Responsibility Skepticism : Attributed CSR Motives’ effect on Consumer Trust and Skepticism - Köykkä, Elli (My University, 2025)
Today's business landscape is hallmarked by consumers' demand for responsible business and growing responsibility reporting from companies. Yet, attempts to move toward sustainability are accompanied by irresponsibility scandals and environmental misdeeds on the part of corporations, resulting in the rise of skepticism and distrust for corporations. Corporate Social Responsibility (CSR) is a widely utilized practice used by companies to display responsibility to an ever-growing degree in the international business market. Despite the potential benefits of CSR to companies and responsible business at large, the observed phenomenon of CSR skepticism undermines its effectiveness. By highlighting the issues within CSR, this thesis explores the role of CSR motives and trust in skepticism through the framework of three-dimensional trust: ability, integrity, and benevolence. This thesis explores why CSR actions can lead to consumer skepticism, how different CSR motives affect trust and skepticism, and how CSR initiatives can build trust through the three dimensions. CSR Consumer skepticism is consumers' disbelief of a company's CSR marketing, -communications, and -operations. Skepticism can negatively impact a corporation and responsible business in multiple ways, particularly by undermining consumer trust, damaging the company’s reputation, and reducing the effectiveness of CSR strategies. Skepticism directed at corporate social responsibility differs from skepticism in other research areas, as it specifically focuses on the attributions of a company’s actions or CSR motives—namely, the perceived reasons behind a company’s engagement in social responsibility. This thesis examines four types of CSR motives: egoistic, values-driven, strategic, and stakeholder-oriented in order to understand the relationship between trust and skepticism. The findings reveal that trust plays a pivotal role in consumer evaluations of CSR. While strategic and value-driven motives can positively influence trust, egotistic and stakeholder-driven motives contribute to skepticism and erode trust. Specifically, egotistic motives are perceived as insincere and exploitative, undermining all three dimensions of trust, while stakeholder motives fail to build integrity or benevolence trust due to their external orientation. Values-driven attributions are perceived by consumers as positive and found to have the potential to create trust, particularly in the dimensions of benevolence and integrity. It is also suggested that consumers are highly tolerant of companies’ economic duties, and thus, strategically attributed CSR has the potential to create trust, especially in the ability dimension of trust. Conversely, CSR actions that align with a company’s expertise, demonstrate consistency with stated values, and reflect a genuine concern for societal welfare can build ability, integrity, and benevolence trust, respectively. These dimensions of trust could ultimately reduce skepticism and foster stronger consumer-company relationships. By examining CSR skepticism through the multidimensional lens of trust, this thesis ultimately aims to provide insight to the discussion of CSR from a stakeholder-driven perspective. The goal is to further develop the understanding of CSR actions as well as CSR motivations in the eyes of consumers. Ultimately contributing to the implementation of more trustworthy CSR overall, benefiting companies, consumers, and sustainable business at large.

Kuluttajat odottavat yrityksiltä yhä enemmän vastuullisuutta ja läpinäkyvyyttä. Liiketoiminnan suunnan muutos näkyy muun muassa yritysten listääntyneessä vastuullisuusraportoinnissa. Tästä huolimatta kansainvälisiä yrityksiä varjostavat vastuuttomuuteen liittyvät skandaalit ja ympäristörikkomukset, jotka horjuttavat yritysten mainetta ja lisäävät kuluttajien epäluottamusta ja skeptisyyttä vastuullisuusraportointia ja yritysvastuu-toimintaa kohtaan. Yritysvastuu (Corporate Social Responsibility, CSR) on laajasti käytetty strateginen työkalu, jonka avulla yritykset pyrkivät osoittamaan vastuullisuuttaan kansainvälisessä liiketoimintaympäristössä. Vaikka yritysvastuulla voi olla merkittäviä hyötyjä niin yrityksille, kuin vastuulliselle liiketoiminnalle, siihen kohdistuva skeptisyys vaikuttaa negatiivisesti yritysvastuun vaikutuksiin. Tämä tutkielma tarkastelee CSR-motiivien ja luottamuksen roolia skeptisyyden lieventämisessä hyödyntäen kolmiulotteista luottamuskehikkoa; arvioiden miten kyvykkyys, rehellisyys ja hyväntahtoisuus vaikuttavat kuluttajien ja yritysten väliseen luottamukseen. Tutkielma vastaa kysymyksiin, miksi CSR-toimenpiteet voivat herättää kuluttajissa skeptisyyttä, miten eri CSR-motiivit vaikuttavat luottamukseen ja skeptisyyteen, ja miten CSR-aloitteilla voidaan rakentaa luottamusta näiden kolmen ulottuvuuden kautta. Kuluttajaskeptisyys on kuluttajien epäuskoa, joka kohdistuu niin yrityksen markkinointiin, viestintään, kuin myös yrityksen toimintaan yleisesti. Skeptisyys voi vaikuttaa negatiivisesti yritykseen ja vastuulliseen liiketoimintaan useilla tavoilla, esimerkiksi heikentämällä kuluttajien luottamusta, yrityksen mainetta ja CSR-strategioiden tehokkuutta. Yritysvastuuseen kohdistuva skeptisyys eroaa muiden tutkimusalueiden skeptisyydestä, sillä se kohdistuu erityisesti yrityksen toiminnan attribuutioihin tai CSR-motiiveihin, eli oletukseen siitä, miksi yritys harjoittaa yritysvastuuta. Tutkielma käsittelee neljää eri CSR-motiivia; egoistinen, arvopohjainen, strateginen ja sidosryhmälähtöinen. Tulokset osoittavat, että luottamus on keskeinen tekijä kuluttajien arvioidessa CSR-toimenpiteitä. Strategiset ja arvolähtöiset motiivit voivat lisätä luottamusta, kun taas egoistiset ja sidosryhmälähtöiset motiivit lisäävät skeptisyyttä ja vahingoittavat luottamusta. Itsekkäät eli egoistiset motiivit koetaan usein epäaitoina ja hyväksikäyttävinä, mikä vaikuttaa negatiivisesti kaikkiin luottamuksen ulottuvuuksiin. Sidosryhmälähtöiset motiivit puolestaan eivät onnistu rakentamaan rehellisyys- tai hyväntahtoisuusluottamusta, sillä ne koetaan ulkoisesti ohjatuiksi. Sen sijaan CSR-toimet, jotka hyödyntävät yrityksen osaamista, noudattavat johdonmukaisesti yrityksen arvoja ja osoittavat aitoa hyväntahtoisuutta yhteiskuntaa kohtaan, voivat rakentaa kyvykkyys-, rehellisyys- ja hyväntahtoisuusluottamusta. Nämä luottamuksen ulottuvuudet voivat vähentää skeptisyyttä ja vahvistaa kuluttajien ja yrityksen välisiä suhteita. Arvopohjaiset motiivit koetaan kuluttajien keskuudessa myönteisinä, ja niiden havaitaan olevan potentiaalisia luottamuksen rakentajia, erityisesti hyväntahtoisuuden ja rehellisyyden ulottuvuuksilla. Tutkielmassa ilmenee, että kuluttajat suhtautuvat erittäin hyväksyvästi yritysten taloudellisiin velvoitteisiin, minkä vuoksi strategisesti kohdistetulla yhteiskuntavastuulla on mahdollisuus vahvistaa luottamusta erityisesti kyvykkyyden ulottuvuudella. Tarkastelemalla CSR-skeptisyyttä luottamuksen moniulotteisen kehikon kautta, tämä tutkielma pyrkii tarjoamaan arvokkaita näkemyksiä CSR-keskusteluun sidosryhmäkeskeisestä näkökulmasta. Tavoitteena on syventää ymmärrystä paitsi CSR-toimenpiteistä, myös niiden taustalla olevista motiiveista kuluttajien näkökulmasta. Tutkielman havainnot voivat tukea luotettavamman yritysvastuun kehittämistä, ollen loppukädessä parempi yritykselle, kuluttajille ja vastuulliselle liiketoiminnalle.
Keywords: CSR, CSR Skepticism, Three-Dimensional Trust, Responsible Business, Consumer Trust